Enhanced Charge Separation Efficiency in DNA Templated Polymer Solar Cells. (18th April 2018) - Toschi, Francesco; Catone, Daniele; O'Keeffe, Patrick; Paladini, Alessandra; Turchini, Stefano; Dagar, Janardan; Brown, Thomas M.
Abstract: The insertion of a DNA nanolayer into polymer based solar cells, between the electron transport layer (ETL) and the active material, is proposed to improve the charge separation efficiency. Complete bulk heterojunction donor–acceptor solar cells of the layered type glass/electrode (indium tin oxide)/ETL/P3HT:PC70 BM/hole transport layer/electrode (Ag) are investigated using femtosecond transient absorption spectroscopy both in the NIR and the UV–vis regions of the spectrum. The transient spectral changes indicate that when the DNA is deposited on the ZnO nanoparticles (ZnO‐NPs) it can imprint a different long range order on the poly(3‐hexylthiophene) (P3HT) polymer with respect to the non‐ZnO‐NPs/DNA containing cells. This leads to a larger delocalization of the initially formed exciton and its faster quenching which is attributed to more efficient exciton dissociation. Finally, the temporal response of the NIR absorption shows that the DNA promotes more efficient production of charge transfer states and free polarons in the P3HT cation indicating that the increased exciton dissociation correlates with increased charge separation. Abstract : Ultrafast pump–probe optical spectroscopy on polymer solar cells of varying composition shows that when DNA is used as a nano‐interlayer between the electron transport (ZnO nanoparticles) and photoactive (P3HT:PC70 BM blend) layers the DNA imprints a long range order on poly(3‐hexylthiophene) (P3HT). Ordered P3HT structures are associated with delocalized singlet excitons which lead to an enhancement of the charge separation efficiency.